Pengaruh Kualitas Pelayanan Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi : Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Serpong Tahun 2019-2023 - Sela Apriani; Lely Suryani (EkoPreneur, 2025)
The purpose of this study is to provide empirical evidence on the effect of servicequality and tax sanctions on individual taxpayer compliance, which plays a criticalrole in supporting the sustainability of a country’s taxation system and ensuring theoptimization of state revenue. The research was conducted on individual taxpayersregistered at the Serpong Primary Tax Service Office (KPP Pratama Serpong)using a probability sampling method, with a total of 100 taxpayers selected as thesample, all of whom are required to report their annual tax returns. This studyapplies a quantitative approach with multiple linear regression analysis as the maintechnique to evaluate the relationship between service quality and tax sanctions asindependent variables, and taxpayer compliance as the dependent variable. Datacollection was carried out through questionnaires distributed directly torespondents, allowing researchers to obtain accurate information about theirperceptions, attitudes, and behaviors regarding tax obligations. The results of theanalysis reveal that service quality and tax sanctions both significantly influencetaxpayer compliance. Specifically, better service quality, demonstrated byresponsive, reliable, and professional tax officers, encourages taxpayers to complywith tax regulations, as it builds trust and reduces administrative difficulties. At thesame time, effective tax sanctions serve as a strong deterrent againstnoncompliance, motivating taxpayers to fulfill their obligations consistently and ontime. These findings highlight the importance of balancing high-quality taxservices with strict enforcement mechanisms, providing valuable insights for taxauthorities and policymakers to strengthen strategies that enhance taxpayercompliance and ultimately contribute to maximizing state revenue throughimproved efficiency in the tax collection system. Keywords: taxpayer compliance, service quality, and tax sanctions